If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5z + 1) + -7 = 55 Reorder the terms: 2(1 + 5z) + -7 = 55 (1 * 2 + 5z * 2) + -7 = 55 (2 + 10z) + -7 = 55 Reorder the terms: 2 + -7 + 10z = 55 Combine like terms: 2 + -7 = -5 -5 + 10z = 55 Solving -5 + 10z = 55 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 10z = 55 + 5 Combine like terms: -5 + 5 = 0 0 + 10z = 55 + 5 10z = 55 + 5 Combine like terms: 55 + 5 = 60 10z = 60 Divide each side by '10'. z = 6 Simplifying z = 6
| 364=a-120 | | x+x+x+x=22 | | 5/6•20 | | 0.4/0.1*22.5=x | | 4(1-3w)=9-7w | | 2(x+1)+4x=4(x-2)+6 | | 8/7x | | 3x-5x-10=-5+4x+3 | | L+3=16 | | .6/1.2=x/200 | | .62x-.25x+.5=.3 | | -13x+19=-6 | | 43x-4/27 | | 9y=5y+6 | | -73=-2x-3(5x-21) | | 0.20x+0.08(x-10)=24.80 | | 2(4.5x-7)=67 | | 17000=x^2-2x+2 | | F(-2)=3x+9 | | -35=-6q+1 | | 4/9x3/5= | | 10x+x=275 | | sin(69)=y(54) | | B/3_1/3 | | 4y^2-0.76*2.0-2y=0 | | -3d-21=0 | | 2x-2=3x-22 | | x/54=cos(69) | | 12-(6s+7)=9-5s | | 2x-9-8x=10 | | 10-n=-6 | | 2d-3=-5 |